Decisions of the Commissioner of Patents and of the United States courts in patent and trade-mark and copyright cases - United States. Patent Office; United States. Department of the Interior; United States. Department of Justice (Washington, U.S. G.P.O., 1869)
"Compiled from Official gazette. Beginning with 1876, the volumes have included also decisions of United States courts, decisions of Secretary of Interior, opinions of Attorney-General, and important decisions of state courts in relation to patents, trade-marks, etc. 1869-94, not in Congressional set." Checklist of U.S. public documents, 1789-1909, p. 530.
Title varies slightly.
Some of the volumes are House documents.
Keywords: Patent laws and legislation -- United States; Trademarks -- United States; Copyright -- United States